2010
DOI: 10.1186/1471-2180-10-37
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and evolutionary comparisons of diazotrophic and pathogenic bacteria of the order Rhizobiales

Abstract: BackgroundSpecies belonging to the Rhizobiales are intriguing and extensively researched for including both bacteria with the ability to fix nitrogen when in symbiosis with leguminous plants and pathogenic bacteria to animals and plants. Similarities between the strategies adopted by pathogenic and symbiotic Rhizobiales have been described, as well as high variability related to events of horizontal gene transfer. Although it is well known that chromosomal rearrangements, mutations and horizontal gene transfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
59
2
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(65 citation statements)
references
References 57 publications
(48 reference statements)
2
59
2
1
Order By: Relevance
“…A tempting hypothesis is that truffle fruiting bodies would be more than a habitat for bacteria and that mutualistic interactions might occur between the fungi and their microbiota. Some members of the Rhizobiales order are well known for their ability to fix atmospheric nitrogen either as freeliving organisms or in symbiosis with plants (26). Barbieri et al (27) demonstrated that nitrogen fixation occurs inside fruiting bodies of the white truffle T. magnatum.…”
Section: Bacterial Communitiesmentioning
confidence: 99%
“…A tempting hypothesis is that truffle fruiting bodies would be more than a habitat for bacteria and that mutualistic interactions might occur between the fungi and their microbiota. Some members of the Rhizobiales order are well known for their ability to fix atmospheric nitrogen either as freeliving organisms or in symbiosis with plants (26). Barbieri et al (27) demonstrated that nitrogen fixation occurs inside fruiting bodies of the white truffle T. magnatum.…”
Section: Bacterial Communitiesmentioning
confidence: 99%
“…Along with the evolution and diversification of animals and plants, the past 500 million years have also witnessed a massive radiation of bacteria. Bacterial lineages have evolved diverse mechanisms to gain entry and proliferate in the tissues and cells of multicellular eukaryotes (1)(2)(3)(4), and these symbionts vary in their effect on hosts from harmful to beneficial (3,4). Archaea have also evolved associations with hosts, but these interactions do not appear as diverse or ubiquitous.…”
mentioning
confidence: 99%
“…Bacterial mutualists are diverse (1)(2)(3)(4)(9)(10)(11)(12) and exhibit a variety of lifestyles and coevolutionary relationships with eukaryote hosts (8) (Table 1). First, beneficial bacteria vary in their degree of reliance on hosts for reproduction.…”
mentioning
confidence: 99%
“…Ozonation decreased the Rhizobiales composition in the planktonic OSPW, while they were still dominant in the biofilm samples. The members of Rhizobiales have diverse functions, including atmospheric nitrogen fixation by living symbiotically in the roots of leguminous plants (55,56). The other dominant orders of Alphaproteobacteria were Rhodospirillales and Rhodobacterales (Fig.…”
Section: Characterization Of Biofilm (I) Confocal Imagingmentioning
confidence: 99%